A 8-year population-based cohort study of irritable bowel syndrome in childhood with history of atopic dermatitis. (26th January 2018) - Tsai, Jeng-Dau; Wang, I-Chung; Shen, Te-Chun; Lin, Cheng-Li; Wei, Chang-Ching
Abstract : Irritable bowel syndrome (IBS) is a chronic functional gastrointestinal disorder affecting a large number of people worldwide. Based on the concept of central sensitization, we conducted a population-based cohort analysis to investigate the risk of IBS in children with atopic dermatitis (AD) as one of the first steps in the atopic march. From 2000 to 2007, 1 20 014 children with newly diagnosed AD and 1 20 014 randomly selected non-AD controls were included in the study. By the end of 2008, incidences of IBS in both cohorts and the AD cohort to non-AD cohort hazard ratios (HRs) and CIs were measured. The incidence of IBS during the study period was 1.45-fold greater (95% CI: 1.32 to 1.59) in the AD cohort than in the non-AD cohort (18.8 vs 12.9 per 10 000 person-years). The AD to non-AD HR of IBS was greater for girls (1.60, 95% CI: 1.39 to 1.85) and children≥12 years (1.59, 95% CI: 1.23 to 2.05). The HR of IBS in AD children increased from 0.84 (95% CI: 0.75 to 0.94) for those with ≤3 AD related visits to 16.7 (95% CI: 14.7 to 18.9) for those with >5 visits (P<0.0001, by the trend test). AD children had a greater risk of developing IBS. Further research is needed to clarify the role of allergy in the pathogenesis of IBS.